2012
DOI: 10.1073/pnas.1202922109
|View full text |Cite
|
Sign up to set email alerts
|

Mutant induced pluripotent stem cell lines recapitulate aspects of TDP-43 proteinopathies and reveal cell-specific vulnerability

Abstract: Transactive response protein is the dominant disease protein in amyotrophic lateral sclerosis (ALS) and a subgroup of frontotemporal lobar degeneration (FTLD-TDP). Identification of mutations in the gene encoding TDP-43 (TARDBP) in familial ALS confirms a mechanistic link between misaccumulation of TDP-43 and neurodegeneration and provides an opportunity to study TDP-43 proteinopathies in human neurons generated from patient fibroblasts by using induced pluripotent stem cells (iPSCs). Here, we report the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
293
3
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 311 publications
(323 citation statements)
references
References 52 publications
24
293
3
3
Order By: Relevance
“…3A). Having established that the level of TDP-43 transcripts do not differ between M337V and CTRL astrocytes, we investigated whether the mutant astrocytes exhibit a cellular and biochemical signature (24) similar to that observed in MN cultures derived from the same iPSC lines (11). Immunoblot analysis showed that M337V astrocytes have significantly more soluble TDP-43 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3A). Having established that the level of TDP-43 transcripts do not differ between M337V and CTRL astrocytes, we investigated whether the mutant astrocytes exhibit a cellular and biochemical signature (24) similar to that observed in MN cultures derived from the same iPSC lines (11). Immunoblot analysis showed that M337V astrocytes have significantly more soluble TDP-43 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A), generated as described (11). NPCs were cultured in suspension as neurospheres in medium containing epidermal growth factor (EGF) and leukemia inhibitory factor (LIF) for 4-6 wk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This evidence indicates that the regulation of the total amount of full-length TDP-43, rather than that of the CTFs, is a critical determinant of cell survival. Indeed, the expression of TDP-43 is elevated in neurons that have differentiated from patient-derived iPS cells that carry the M337V mutation 24 . Furthermore, TDP-43 proteins that are mutated have longer half-lives than the wild-type protein and these longer half-lives correlate with a more rapid onset of the disease 10,25 .…”
Section: Discussionmentioning
confidence: 99%